1989
DOI: 10.4319/lo.1989.34.7.1263
|View full text |Cite
|
Sign up to set email alerts
|

The effects of patch size and substrate isolation on colonization modes and rates in an intertidal sediment

Abstract: The dynamics of soft-bottom disturbance mosaics may be strongly influenced by life stages of colonists, disturbance size, and patch isolation. We assessed the effects of postlarval immigration, patch size, and vertical isolation on colonization following small-scale disturbance in a mudflat in Barnstable Harbor, Massachusetts. Defaunated sediment plugs of two sizes (50 and 1,750 cm2 in plan area) and two levels of isolation (flush with the seafloor and elevated 5 cm) were implanted in the flat and sampled afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
78
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 30 publications
2
78
0
1
Order By: Relevance
“…This is because, litter from riparian vegetation is a primary source of coarse particulate organic matter (CPOM) to aquatic systems (Carvalho and Uieda, 2004). However, in low-gradient Coastal Plain streams much of the CPOM becomes buried within the sandy stream beds following floods (Smith and Brumsickle, 1989). Leaf litter on the surface of perennial stream beds function primarily as a food source, whereas buried litter or wood additions have had strong invertebrate response (Turner et al, 1997), no response (William, 1977), or a variable response over time (Tillman et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This is because, litter from riparian vegetation is a primary source of coarse particulate organic matter (CPOM) to aquatic systems (Carvalho and Uieda, 2004). However, in low-gradient Coastal Plain streams much of the CPOM becomes buried within the sandy stream beds following floods (Smith and Brumsickle, 1989). Leaf litter on the surface of perennial stream beds function primarily as a food source, whereas buried litter or wood additions have had strong invertebrate response (Turner et al, 1997), no response (William, 1977), or a variable response over time (Tillman et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…이와 같은 이유로 모 래갯벌과 같이 수력학적으로 역동적 조건을 가진 서식처일수록 물 리적 교란 이후 재군집화 및 회복 과정이 빠르게 진행되는 것으 로 알려져 있다. 두 번째 요인은 발생한 교란의 규모로 교란된 면 적이 넓을수록 재점유와 회복에 걸리는 시간이 오래 걸리는 것으 로 보고된 바 있다 (Smith and Brumsickle, 1989). 세 번째 요인은 교란지역과 주변해역에 서식하는 종들의 생활사 및 서식습성 등 의 개체군 특성으로 수역학적 조건과 결합하여 군집의 재점유와 천이과정에 결정적인 역할을 하는 것으로 알려져 있다 (Zajac and Whitlatch, 1985;Shull 1997).…”
unclassified
“…If this were the case, then the size-and stage-structure of colonists in new patches should resemble those in established patches, and sizes and reproductive maturity should not increase significantly with increasing patch age (Shull 1997). Alternatively, were the patch colonised by settlement of larvae or by migration of a nonrepresentative subset of the background population, patches opened at different times might be colonised by different cohorts, and differ in their age-and sizestructures (Levin 1984, Smith & Brumsickle 1989. Specifically, our aims were to (1) test whether the ageand stage-structure of alvinellid colonists in new patches differs from those of the established population, (2) test whether the age-and stage-structure of colonists increases with increasing patch age, and (3) determine whether the age-and stage-structure of colonists are consistent with the migration of a representative subset of the background population, or with the migration of a non-representative subset, for instance through larval settlement.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of mosaic communities from shallow-water or deep-sea environments have shown that disturbed or new patches may be colonised by several pathways: settlement of larvae from the water column, reproduction within or close to the patch by species with benthic development, or immigration of benthic juveniles or adults from adjacent areas (Santos & Simon 1980, Levin 1984, Smith & Brumsickle 1989, Shull 1997, Airoldi 2000. Whether colonists arrive as larvae, as juveniles, or adults may result in distinct communitydevelopment patterns (Sousa 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation